EKSPLORASI PRAKTIK REFLEKTIF GURU SEKOLAH DASAR DALAM MENINGKATKAN KUALITAS PEMBELAJARAN - Prisilia, Sindi Regina; Arie Rakhmat Riyadi, Neni Maulidah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore reflective practices carried out by elementary school teachers in an effort to improve the quality of learning. This study uses a qualitative approach with a phenomenological method. The subjects of the study were grade III and IV teachers at SD Negeri 128 Haurpancuh who had routinely implemented reflective practices. Data collection techniques were carried out through in-depth interviews and classroom observations. The results of the study showed that teachers reflected individually and collaboratively, both through teaching journals and discussions with colleagues. Reflective practices have an impact on improving learning planning, more adaptive classroom management, and increasing student engagement. Reflection also helps teachers understand students' learning needs and improve professional competence sustainably.